PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 021 BAGAN BARAT KECAMATAN BANGKO LABUPATEN ROKAN HILIR YEARS 2015/2016 - Maria R '; Mahmud alpusari; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :The problem in this Class Action Research is Are Applying inquiry learning model can improve learning outcomes fifth grade science students Elementary School 021 West Bagan. For that we need to be improved in order to improve learning outcomes. Efforts to repair is done by applying Inquiry Learning Model. The experiment was conducted in classes V Elementary School 021 West Exhibit, the number of students 21 students consisted of 9 male students and 12 female students. Data collection techniques were used that observation techniques and test engineering. Data analysis technique used is the result of learning, completeness individual and classical, the activities of teachers and students, individual awards. The results showed that the initial data is known that the students' social studies students only in an average 63.14 and completeness achieved by 23.8% with less category. In the first cycle and the class action after being evacuated there was little increase student learning outcomes IPA with an average of 73.9 and classical completeness still reached 71.42% with enough category. Seeing the conditions achieved in the first cycle of meetings 1 and 2, the researchers took the initiative to proceed to the second cycle. After the implementation of learning science in this second cycle learning outcomes achieved by students which averaged 78.3 and classical completeness of 85.71% with a very good category. This means that the inquiry learning model is one of the effective learning methods to improve learning outcomes fifth grade science students Elementary School 021 West Bagan, Bangko Subdistrict, Rokan Hilir.Keywords : Inquiry Learning Model , Science Learning Outcomes